Depression in 3/6‐year‐old children: clinical and psychosocial outcomes in later childhood and adolescence. (2nd December 2021) - Silver, Jamilah; Olino, Thomas M.; Carlson, Gabrielle A.; Dougherty, Lea R.; Bufferd, Sara J.; Klein, Daniel N.
Abstract : Background: In recent years, epidemiological and clinical studies have revealed that depressive disorders can present in early childhood. To clarify the validity and prognostic significance of early childhood‐onset depression, we investigated diagnostic and functional outcomes in later childhood and adolescence. Methods: A community sample ( N  = 516) was assessed for psychopathology at ages 3 and 6 using the Preschool Age Psychiatric Assessment. When participants were 9, 12, and 15 years old, children and parents completed the Kiddie Schedule for Affective Disorders and Schizophrenia and measures of symptoms and functioning. Results: In models adjusting for covariates, depressed 3/6‐year‐old children were more likely to experience subsequent episodes of depressive disorders and exhibited significantly higher rates of later anxiety disorder, attention deficit hyperactivity disorder, and suicidality compared to children without depressive disorders at age 3/6. Early childhood depression was also associated with higher levels of mother, but not child, reported depressive symptoms at age 15 compared to children without depressive disorders at age 3/6. Finally, depression at age 3/6 predicted lower levels of global and interpersonal functioning and higher rates of treatment at age 15 compared to children without depressive disorders at age 3/6. Conclusions: Results support the clinical significance of depression in 3/6‐year‐old children, although further studies with larger samples are needed.